2014
DOI: 10.3892/mmr.2014.3115
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of induced pluripotent stem cell-conditioned medium on in vitro hypertrophic scarring fibroblast activation

Abstract: Hypertrophic scarring (HS) is a type of fibrosis that occurs in the skin, and is characterized by fibroblast activation and excessive collagen production. However, at present, therapeutic strategies for this condition are ineffective. Previous studies have identified that the mutual regulation of chronic inflammation, mechanical force and fibroblast activation leads to the formation of HS. Induced pluripotent stem cells (iPSCs) are novel bioengineered embryonic-like stem cells, initially created from mouse adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The exaggerated inflammatory phase is closely associated with HS development, in which inflammatory cells such as neutrophils, macrophages and T-lymphocytes migrate to the wound site with high secretion of various cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6 and transforming growth factor (TGF)-β1 ( 7 , 9 , 10 ). Specific cytokines and inflammatory factors, such as TGF-β1, contribute to fibroblast activation and the modulation of the fibroblast phenotype ( 11 ). Many studies have reported that overactivation of dermal fibroblasts is involved in the process of HS formation ( 7 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The exaggerated inflammatory phase is closely associated with HS development, in which inflammatory cells such as neutrophils, macrophages and T-lymphocytes migrate to the wound site with high secretion of various cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6 and transforming growth factor (TGF)-β1 ( 7 , 9 , 10 ). Specific cytokines and inflammatory factors, such as TGF-β1, contribute to fibroblast activation and the modulation of the fibroblast phenotype ( 11 ). Many studies have reported that overactivation of dermal fibroblasts is involved in the process of HS formation ( 7 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of induced pluripotent stem cellconditioned medium appears to reduce levels of type I (adult) collagen and attenuates the local inflammatory cell response in vitro. 103 Additionally, mesenchymal stromal cells may have the ability to be reprogrammed into sweat glandlike cells, offering the potential to restore injured adnexal structures from deep burn injuries. 104 …”
Section: Stem Cellsmentioning
confidence: 99%
“…The role of miRNAs in skin development and pathology has been extensively researched. Several previous reports have indicated the involvement of miRNAs in the regulation of HS formation ( 11 , 28 30 ). However, limited information regarding the roles of miRNAs in fetal KC-induced alterations in HSFbs is available ( 31 ).…”
Section: Discussionmentioning
confidence: 94%